The Meaning of Rajah and Its Impact: A Study of Indonesian Madurese Tribes’ Belief in Kepping Classic Holy Book Based on Genetic Structuralism Lucius Goldmann - Basid, Abdul; Hermanda, Anilla Febriaty (Faculty of Tarbiyah and Teacher Training, IAIN Jember, 2019)
Abstract Rajah’ is one of the ancestor’s legacy which use by Madura’s people, expecially who in Islamic boarding school of holy book until nowdays. ‘Rajah’ is still believed as one of amulet to keep a traditional holy book’s from termite, one species of the insect. This study wants to know and to investigate the opinion of Madura’s people about ‘rajah’ to their credibility to keep the traditional holy book’s based on genetic structuralism’s perspective. The results of this study are: a) the facts of humanity expresses when people put rajah in their holy books, their holy books will not be eaten by termite; b) collective subject represents teacher’s order to write rajah; c) worldview elaborates the function of rajah will work if the user believe in it; d) the structure of literary reflects one’s believe in the truth happening after they use rajah; and e) the dialectical method of understanding explanations refers to all available concepts. Thus, we can understand from facts of humanity, worldview, and structure of literary.